Financial Management and Policy / Sixth Edition - Van Horne James C (Prentice Hall, 1983)
Preface, Foundations of Finance, Goals and Functions of Finance, Concepts in Valuation, Valuation of a Firm's Stock, Valuation from a Relative Standpoint, Investment in Assets and Required Returns, Principles of Capital Investment, Other Dimensions to Capital Budgeting, Evaluation of Risky Investments: Required Returns for Projects, Required Returns for Companies and Divisions and Acquisitions, Financing and Dividend Policies, Theory of Capital Structure, Making Capital Structure Decisions, Dividend-Payout Ratio and Valuation, Other Aspects of Dividend Policy, Management of Liquidity and Current Assets, Management of Cash and Marketable Securities, Short- and Intermediate- Term Finance, Secured Loans and Term Financing, Lease Financing, Long-Term Financing, Issuing Securities, Expansion and Contraction, Corporate Restructuring, Financial Distress, Tools of Financial Analysis and Control, Financial Ratio Analysis, Financial Planning, Appendix, Index.
Preface, Foundations of Finance, Goals and Functions of Finance, Concepts in Valuation, Valuation of a Firm's Stock, Valuation from a Relative Standpoint, Investment in Assets and Required Returns, Principles of Capital Investment, Other Dimensions to Capital Budgeting, Evaluation of Risky Investments: Required Returns for Projects, Required Returns for Companies and Divisions and Acquisitions, Financing and Dividend Policies, Theory of Capital Structure, Making Capital Structure Decisions, Dividend-Payout Ratio and Valuation, Other Aspects of Dividend Policy, Management of Liquidity and Current Assets, Management of Cash and Marketable Securities, Short- and Intermediate- Term Finance, Secured Loans and Term Financing, Lease Financing, Long-Term Financing, Issuing Securities, Expansion and Contraction, Corporate Restructuring, Financial Distress, Tools of Financial Analysis and Control, Financial Ratio Analysis, Financial Planning, Appendix, Index.